Mental health of women in deprivation of liberty: their perception (Research, Society and Development, 2021)
This article aims to understand the perception of women deprived of freedom about their mental health. A descriptive study with a qualitative approach was carried out, using semi-structured interviews that were recorded with eight women deprived of their freedom in a closed regime in a prison in the interior of the south of the country. We observed in this study that women deprived of freedom experience feelings such as loneliness, anguish, homesickness, worry, irritation, fear and isolation. During this moment, having a strong impact on their mental health, suicidal thoughts and acts were observed. The women in this research have different support networks during the deprivation of freedom, ranging from family members and friends present to their abandonment. The relationship between these women is seen as healthy, they report being helpful to each other, and some said that they restrict the conversation with their colleagues to what is necessary to maintain a good relationship and avoid conflicts. As a form of distraction during incarceration, they carry out activities through a project, they also reported watching TV, radio and cleaning the cell, but they stated that it would be important to carry out other activities, mainly professional and educational, and also promotional activities your health. Thus, it is observed how much is necessary a multidisciplinary monitoring with a view to the comprehensive health and education of these women.